Learning Model in Islamic Education Park (TEK): Early Children’s Tawaf Learning Desaign In Syariah Tourism Park Pamah Simelir - Hemawati, Hemawati; Holid, Syahrul (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2024)
The aim of this research is 1) to find the concept of an Islamic educational park in the Pamah Simelir Langkat sharia tourist park (TWS). 2) Designing learning for early childhood that can be done at the Sharia Tourism Park (TWS) as a model for an Islamic Education Park (TEK). 3) Developing a learning model at the Pamah Simelir Islamic Education Park (TEK) sharia tourism park (TWS). This type of research is Research and Development (R&D) to produce a concept and learning model for early childhood because the final aim of this research is to find the concept and model of tawaf learning for early childhood in a sharia tourism park as an Islamic education park (TEK). The research results show that 1) The concept of an Islamic educational park in a Sharia Tourism Park: Recreation, Glamping, Education Park which provides comfort in recreation through the freshness of nature by providing visitors with knowledge of facilities with Islamic nuances. The design of the learning model in the Pamah Simelir Islamic Education Park (TEK) is designed with tawaf learning in mind for early childhood. 2) The steps for implementing tawaf learning practices in sharia tourist parks are carried out in 5 major steps, namely: 1) preparation at school, 2) preparation at the location before entering the location, 3) Preparation of Clothing and Equipment, 4) Implementation of Tawaf Practice Activities. The process of implementing the practice of tawaf is carried out 7 times, and 5) Closing. 3) The design of the learning model at the Islamic Education Park (TEK) Pamah Simelir Sharia tourist park for early childhood has met the requirements, namely; suitable as a learning park, effective for improving learning skills, and practical for use by the community in terms of tawaf learning for early childhood